Half Moon Bay : a novel - LaPlante, Alice, 1958- (Scribner, 2018)
"A smart, haunting tale of psychological suspense from the award-winning New York Times bestselling author of Turn of Mind. Jane loses everything when her teenage daughter is killed in a senseless accident. Jane is devastated, but sometime later, she makes one tiny stab at a new life: she moves from San Francisco to the tiny seaside town of Half Moon Bay. She is inconsolable, and yet, as the months go by, she is able to cobble together some version of a job, of friends, of the possibility of peace. And then, children begin to disappear. And soon, Jane sees her own pain reflected in all the parents in the town. She wonders if she will be able to live through the aching loss, the fear all around her. But as the disappearances continue, she begins to see that what her neighbors are wondering is if it is Jane herself who has unleashed the horror of loss. Half Moon Bay is a chilling story about a mother haunted by her past. As Stewart O'Nan said about Turn of Mind--this novel "blindfolds the reader and spins her around.""--